Undergraduate medical education interventions aimed at managing patients with obesity: A systematic review of educational effectiveness. (11th August 2021) - Katz, Nathan J.; Neary, Emma; Tang, Natasha; Braund, Heather; Cofie, Nicholas; Zevin, Boris
Summary: The growing obesity epidemic requires an evidence‐based approach to management of patients with obesity. Two systematic reviews on obesity‐management interventions in undergraduate medical education, both published in 2012, reported discrepant findings. This study aimed to build on previous research by identifying, systematically reviewing, and synthesizing current literature on the effectiveness of educational interventions aimed at teaching management of patients with obesity to medical students. A comprehensive search of seven databases was performed with no date or language restrictions. Database search identified 6462 studies; 5373 were screened against title and abstract, 156 full‐text articles were retrieved, 31 met eligibility criteria, and 17 were included after critical appraisal of study methodology. Nine cohort‐studies, three qualitative, two case–controls, two mixed‐methods, and one randomized controlled trial were included. Findings supported the educational effectiveness of brief (<3 h) educational interventions, the value of video‐clips to deliver content, and the importance of in‐person teaching. Findings also demonstrated an increase in the number of studies describing educational interventions aimed at teaching management of patients with obesity to medical students. These results can be used by medical educators to inform the design of educationally effective curricula focused on the management of patients with obesity in undergraduate medical education.